CORRIGENDUM - UB, IJRI (International Journal of Radiology and Imaging, 2024)
Corrigendum to: “NEUROLOGIC COMPLICATION IN LUNG ADENOCARCINOMA EFGR MUTATION WITH A CONSOLIDATION-TO-TUMOR-RATIO (CTR) >75%” (International Journal of Radiology and Imaging. 02. (02). 28 Desember 2023. 24-28)